An Experimental Simulation of Heat Effects on Cognition and Workload of Surgical Team Members - Ward, Mary K.; Yam, C.M.H.; Palejwala, Z.; Wallman, K.; Taggart, S.M.; Wood, F.M.; Parker, Sharon (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Objective: To isolate heat exposure as a cause of cognitive impairment and increased subjective workload in burns surgical teams. Summary of Background Data: Raising ambient temperature of the operating room can improve burns patient outcomes, but risks increased cognitive impairment and workload of surgical team members. Prior research indicates ambient heat exposure depletes physiological and cognitive resources, but these findings have not been studied in the context of burns surgical teams. Methods: Seventeen surgical team members completed 2 surgery simulations of similar complexities in a hot and in a normothermic operating room. During each simulation, participants completed multiple cognitive tests to assess cognitive functioning and the SURG-TLX to self-assess workload. Order effects, core body temperature changes due to menstruation, and circadian rhythms were controlled for in the experimental design. Descriptive statistics, correlations, and mixed ANOVAs were performed to assess relationships between ambient heat exposure with cognitive functioning and perceived workload. Results: Heat had a main effect on executive functioning and verbal reasoning. Duration of heat exposure (heat * time) increased response times and negatively impacted executive functioning, spatial planning, and mental rotation. Perceived workload was higher in the hot condition. Conclusions: We provide causal evidence that over time, heat exposure impairs cognitive speed and accuracy, and increases subjective workload. We recommend building on this study to drive best-practices for acute burns surgery and design work to enable burns teams to maintain their cognitive stamina, lower their workload, and improve outcomes for patients and surgeons.